2018
DOI: 10.14202/vetworld.2018.1120-1126
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic characterization of the native rabbits in Middle Egypt

Abstract: Aim:Native rabbits in smallholder system are considered as important genetic resources, and the present study was aimed to study the genetic and phenotypic characterization and detection of the maternal origin of the native rabbit populations located at the Middle of Egypt.Materials and Methods:A survey of native rabbit populations was conducted in three governorates (Fayum [FY], Beni Suef [BN], and El Menia [MN]). The phenotypic characterization of rabbits included the profile body of the head, ears, eyes, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
2
9
2
Order By: Relevance
“…However, the high inbreeding values can be attributed to non-random mating and some loci might be linked to some economically selected traits. Our results were consistent with those of (El-Aksher et al, 2017;Abdel-Kafy et al, 2018), who reported moderate positive values for F IS (0.083 and 0.073 respectively).…”
Section: Polymorphism Of Microsatellite Loci In the Breeds Studiedsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the high inbreeding values can be attributed to non-random mating and some loci might be linked to some economically selected traits. Our results were consistent with those of (El-Aksher et al, 2017;Abdel-Kafy et al, 2018), who reported moderate positive values for F IS (0.083 and 0.073 respectively).…”
Section: Polymorphism Of Microsatellite Loci In the Breeds Studiedsupporting
confidence: 93%
“…The PIC values in all studied loci ranged from 0.351 at locus SAT2 to 0.846 at locus SOL33 with an average of 0.710. The average PIC value of our study was higher (0.689) than that recorded by Abdel-Kafy et al (2018), who evaluated 8 loci across 3 Egyptian rabbit populations, and lower than (0.760) that recorded by El-Aksher et al (2017), who evaluated 16 microsatellite loci across 4 rabbits populations. The values of our study could suggest their usefulness for genetic diversity studies and linkage mapping programmes in Egyptian rabbits.…”
Section: Polymorphism Of Microsatellite Loci In the Breeds Studiedcontrasting
confidence: 86%
See 1 more Smart Citation
“…SSR markers are commonly used to reveal genetic diversity because they are abundant, distributed through genome randomly, easy to access and apply, highly polymorphic, and show codominant inheritance. SSR markers were used to detect genetic diversity or parentage test in different livestock including cattle (Demir and Balcioglu, 2019), sheep (Ocampo et al, 2016), goat (Jawasreh et al, 2018, pigs (Szmatoła et al, 2016), horses (Semik and Zabek, 2013) chickens (Karsli and Balcioglu, 2019), rabbit (Abdel-Kayf et. al., 2016), ducks (Hariyono et al, 2019, and donkeys (Han et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This study reported what they termed as “directional loss in genetic diversity” from the wild rabbits in the Iberian Peninsula, heterozygosity (He) 0.825 to the domestic rabbits in France heterozygosity (He) 0.581. In another study, [1, 12] utilized microsatellites and mtDNA cytochrome b, respectively, in the study of genetic diversity of the rabbit. The former reported that wild rabbits from France were grouped together with wild rabbits from the Iberian Peninsula, whereas [12] revealed that the rabbits under the study belonged to lineage A, except a single rabbit that belonged to lineage G. Lineage A is the major lineage among wild rabbit populations, while lineage G is rarely reported in the studies on origin of rabbits.…”
Section: Introductionmentioning
confidence: 99%